2018
DOI: 10.1136/jim-2018-000715
|View full text |Cite
|
Sign up to set email alerts
|

Children with Allergic Diseases Have An Increased Subsequent Risk of Migraine upon Reaching School Age

Abstract: The association between migraine and allergy has remained a subject of debate for more than a century. To systemically investigate the interaction between children with antecedent allergic diseases and their future risks of migraine on reaching school age, we recruited 16,130 children aged 7-18 with migraine diagnosed between 2000 and 2008, and 64,520 matched controls without a history of migraine. The ORs of migraine were calculated for the association with allergic diseases diagnosed before migraine diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…It is possible that individuals with severe AD have a higher prevalence of adverse cardiovascular events because of shared associated factors such as obesity, smoking, hypertension, and diabetes. Migraine has previously been linked to allergic diseases such as asthma and allergic rhinitis, and some studies have reported an association with AD in children and adolescents as well [7,8]. Our study adds new knowledge about the increased prevalence of migraine and headache in adults with AD.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…It is possible that individuals with severe AD have a higher prevalence of adverse cardiovascular events because of shared associated factors such as obesity, smoking, hypertension, and diabetes. Migraine has previously been linked to allergic diseases such as asthma and allergic rhinitis, and some studies have reported an association with AD in children and adolescents as well [7,8]. Our study adds new knowledge about the increased prevalence of migraine and headache in adults with AD.…”
Section: Discussionmentioning
confidence: 55%
“…Migraine has previously been linked to allergic diseases such as asthma and allergic rhinitis, and some studies have reported an association with AD in children and adolescents as well [ 7 , 8 ]. Our study adds new knowledge about the increased prevalence of migraine and headache in adults with AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have correlated allergic rhinitis with migraine in childhood, pointing either to a prominent prevalence of the latter in patients with atopy 10 , or to a higher than expected frequency of allergic conditions in migraineurs 5,7-9 . The susceptibility for developing migraine in children suffering from allergic rhinitis was also suggested 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this relationship may be bidirectional, two longitudinal surveys from Taiwan have reported a higher risk of developing migraine in atopic children in comparison with nonatopic children, especially those with allergic rhinitis 11,12 , suggesting a role of the immune system in the manifestation of migraine. On the other hand, anti-asthmatic and anti-allergic therapies were associated with decreased risk of migraine in children and adolescents 8 .…”
mentioning
confidence: 99%